Hitler's Commanders: Officers of the Wehrmacht, the Luftwaffe, the Kriegsmarine, and the Waffen-SS - Mitcham, Samuel W.; Mueller, Gene (Rowman & Littlefield Publishers, 2012)
Despite huge odds against them, Hitler’s commanders—the elite of the Wehrmacht—almost succeeded in conquering Europe. Now in an expanded edition that includes biographies of the generals of Stalingrad and a new chapter on the panzer commanders, this book offers rare insight into the men who ran Nazi Germany’s war machine. Going beyond common stereotypes, Samuel W. Mitcham and Gene Mueller recount the compelling lives of a varied group of army, navy, Luftwaffe, and SS men, including their early life, their military exploits during the war, and their post-war career, if any. Weaving in dramatic stories of tank commanders, fighter pilots in aerial combat, and U-Boat aces, the authors bring the battlefields of World War II to life.